Chemo‐Biological Upcycling of Poly(ethylene terephthalate) to Multifunctional Coating Materials. Issue 19 (26th August 2021) - Kim, Hee Taek; Hee Ryu, Mi; Jung, Ye Jean; Lim, Sooyoung; Song, Hye Min; Park, Jeyoung; Hwang, Sung Yeon; Lee, Hoe‐Suk; Yeon, Young Joo; Sung, Bong Hyun; Bornscheuer, Uwe T.; Park, Si Jae; et al.
Abstract: Chemo‐biological upcycling of poly(ethylene terephthalate) (PET) developed in this study includes the following key steps: chemo‐enzymatic PET depolymerization, biotransformation of terephthalic acid (TPA) into catechol, and its application as a coating agent. Monomeric units were first produced through PET glycolysis into bis(2‐hydroxyethyl) terephthalate (BHET), mono(2‐hydroxyethyl) terephthalate (MHET), and PET oligomers, and enzymatic hydrolysis of these glycolyzed products using Bacillus subtilis esterase (Bs2Est). Bs2Est efficiently hydrolyzed glycolyzed products into TPA as a key enzyme for chemo‐enzymatic depolymerization. Furthermore, catechol solution produced from TPA via a whole‐cell biotransformation ( Escherichia coli ) could be directly used for functional coating on various substrates after simple cell removal from the culture medium without further purification and water‐evaporation. This work demonstrates a proof‐of‐concept of a PET upcycling strategy via a combination of chemo‐biological conversion of PET waste into multifunctional coating materials. Abstract : PETit four : A proof‐of‐concept upcycling strategy to convert poly(ethylene terephthalate) (PET) into multifunctional catechol coating materials is presented: (1) PET glycolysis without purification; (2) one‐step enzymatic hydrolysis of glycolyzed products into terephthalic acid (TPA); (3) whole‐cell biotransformation of TPA into catechol using an engineered Escherichia coli ; (4) application of crude catechol solution as a multifunctional coating material without purification.